2010
DOI: 10.1037/a0019787
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the psychotherapy phase model to clinically significant deterioration.

Abstract: While previous research on deterioration has focused on identifying individuals at risk for negative outcomes, little is known about the nature or pattern by which deterioration occurs. The problem of deterioration is especially salient in training clinics; a setting in which higher deterioration rates have been reported. Two studies were designed to test the applicability of the phase model to deterioration in a training clinic and to replicate the model with a training clinic referral-base sample. In Study 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…At the same time, a large proportion of patients (approximately 66%) still reported interpersonal problems (i.e., with scores in the dysfunctional range) at follow-up. This finding is in line with the posttreatment outcomes of this very sample (Lopes et al, 2013), with the phase model (Howard et al, 1993;Swift et al, 2010) and with previous research comparing the course of depressive symptoms and interpersonal problems during and after treatment (Barkham et al, 2002(Barkham et al, , 1993(Barkham et al, , 1996Hilsenroth et al, 2001;Kopta et al, 1994;Vromans and Schweitzer, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At the same time, a large proportion of patients (approximately 66%) still reported interpersonal problems (i.e., with scores in the dysfunctional range) at follow-up. This finding is in line with the posttreatment outcomes of this very sample (Lopes et al, 2013), with the phase model (Howard et al, 1993;Swift et al, 2010) and with previous research comparing the course of depressive symptoms and interpersonal problems during and after treatment (Barkham et al, 2002(Barkham et al, , 1993(Barkham et al, , 1996Hilsenroth et al, 2001;Kopta et al, 1994;Vromans and Schweitzer, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…In daily practice, clinicians frequently observe that symptomatic change occurs faster than changes on interpersonal levels (e.g., interpersonal problems, dysfunctional relationship patterns). Accordingly, the phase model of change (Howard et al, 1993;Swift et al, 2010) suggests that interpersonal improvements will take longer to achieve when compared to symptomatic improvements. Research examining brief treatments supports this observation.…”
Section: Symptomatic Vs Interpersonal Change In Depressionmentioning
confidence: 99%
“…The phase model was empirically supported by the results indicating that remoralization preceded remediation, which in turn preceded rehabilitation (Hilsenroth, Ackerman, & Blagys, 2001;Howard et al, 1993;Swift, Callahan, Heath, Herbert, & Levine, 2010). Consistent with the phase model, Kopta et al (1994) found different patterns of recovery for different clusters of symptoms, with acute distress requiring less time to recover (five sessions for 50% of the clients) than chronic distress (14 sessions for 50% of the clients).…”
Section: Symptomatic Versus Interpersonal Change In Psychotherapymentioning
confidence: 62%
“…For a comparison with the results obtained by Kopta et al (1994) and Barkham et al (1996), we assume that the OQ-45.2 IR subscale is equivalent to the 'characterological' symptoms, which are interpersonal in nature. In the phase model, it would reflect the rehabilitation phase (Hilsenroth et al, 2001;Howard et al, 1993;Swift et al, 2010).…”
Section: Structured Clinical Interview For Diagnostic and Statisticalmentioning
confidence: 99%
“…One such process that the phase model of improvement has been applied to is deterioration. Based on the rationale that deterioration is likely characterized by what in essence is an inverted phase model, one study found that a reverse phase model (which was composed of the sequential processes of dehabilitation, demediation, and demoralization) was applicable to two samples; one community sample of university undergraduates and one clinical sample of individuals attending a university-based psychology clinic (Swift, Callahan, Heath, & Herbert, 2010). Some of the data gathered for the paper indicated that individuals who deteriorated in psychotherapy exhibited increased symptoms (demediation) followed by demoralization or dehabilitation, with no specific ordering of these phases being observed.…”
Section: The Phase Model Applied Beyond Therapeutic Improvementmentioning
confidence: 99%